Minnesota Multiphasic Personality Inventory (MMPI-2) profiles in the assessment of ovum donors - Klock, Susan C.; Covington, Sharon N. (Fertility and sterility, 2010)
To examine the relationship between MMPI-2 scores and oocyte donation outcome. Descriptive chart review. Two oocyte donation programs. Five hundred anonymous oocyte donor applicants. None. Demographics, MMPI-2 scores and donation outcome. The mean age was 26.6 years, 54% were Caucasian, 37% were high school graduates with some college, 55% were single, and 49% were nulliparous. Fifty-nine percent of donors completed at least one donation cycle, 10% were ruled out because of medical concerns, 12% dropped out, 11% were ruled-out because of psychologic concerns, and 8% had not been selected by a recipient. On the MMPI-2, the mean profile was in the normal range. Significant differences were found between groups on subscales F, F(p), L, S, S1, 2, 4, 8, and 9. The largest differences in scores between donors who completed a cycle and those who were psychologically excluded were on L (8 points) and 9 (6 points). Use of the non-K corrected scores replicated group differences. MMPI-2 scores differed between donors who completed a donation cycle and those who were psychologically excluded. Attention should be paid to validity scale L when considering donor selection.